(untitled) (PerCursos, 2025)
This paper analyzes Venezuelan migration to Brazil, with a specific focus on the internal relocation [interiorização] strategy and the migration policies implemented by the Brazilian government under the framework of Operation Welcome [Operação Acolhida], aimed at directing Venezuelan migration from the northern border to other regions of the country. These processes occur in a period marked by new dynamics of international migration in Brazil, highlighting three aspects: a new regulatory framework based on the 2017 Migration Law, an increase in the number of immigrants in the 2010s, and the emergence of the southern region of the country as the main destination for international migration. The study seeks to analyze the western region of the state of Santa Catarina, in the south of Brazil, where the presence of Venezuelan migrants is more significant and which is notable for the presence of the meatpacking industry, one of the main employment sectors for immigrants. Finally, the study explores some important concepts to address this process, such as crisis migrations and directed migrations, discussing how the humanitarian context relates to migration policies and affects the dynamics of labor recruitment.